BIOPORE EFFECTIVENESS IN INCREASING SOIL ORGANIC CARBON AND ADDRESSING ENVIRONMENTAL ISSUES - Putra, Farhan Akmala; Santoso, Siswanto Imam; Setiadi, Agus; Saputra, Andre Dika; Putra Pradana, Wakhid Ikhfannida Cahya; Rizki, Jovan Rafi (Institut Teknologi Nasional, Bandung, 2026)
The study, conducted in May 2024, focused on searching the Scopus.com database for literature on biopores, resulting in 208 articles published between 1985 and 2024 as the final dataset. Metadata was obtained from Scopus.com and analyzed descriptively. The dataset was exported into Excel CSV format and subsequently processed using VOSViewer (VV) version 1.6.20 to provide a clear overview of the research landscape. Findings revealed variations in the number of publications on biopores over time, with Kautz recognized as the most prolific scholar. The main publication outlets included the IOP Conference Series: Earth and Environmental Science, Soil and Tillage Research, and Geoderma. The dominant document categories were journal articles, conference proceedings, and reviews. Germany, the United States, and Indonesia emerged as the leading contributors to biopore-related research. Influential institutions in this field were the University of Bonn, Leibniz Centre for Agricultural Landscape Research (ZALF e.V.), and the University of Copenhagen. The results further indicated that biopores contribute significantly to enhancing soil organic carbon, thereby improving soil fertility and agricultural productivity. Moreover, biopores were shown to be an effective approach for managing organic waste by transforming it into compost, which in turn supports higher land productivity.